Interleukin 6 and 8 Levels in Plasma and Fibroblast Cultures in Psoriasis (Hindawi Limited, 2006)
Fibroblasts have been implicated in psoriatic inflammatory processes. The aim of the study was to evaluate soluble interleukin 2 receptor (sIL-2R), interleukin 6 (IL-6), and interleukin 8 (IL-8) plasma levels in psoriatic patients and IL-6 and IL-8 levels in fibroblast culture supernatants. Cytokines levels in plasma and supernatants were measured by ELISA. Plasma sIL-2R, IL-6, and IL-8 levels were higher before the treatment in comparison to healthy controls (<mml:math alttext="$P<0.001$"> P < 0.001 ) and decreased after treatment. Fibroblasts from healthy controls, psoriatic lesional skin, and noninvolved psoriatic skin, when stimulated with tumor necrosis factor alpha, released considerable amounts of IL-6 and IL-8. No significant difference between healthy controls and psoriatic fibroblasts was observed. Monitoring plasma sIL-2R levels could be employed as a reliable method of psoriasis activity. IL-8 and IL-6 plasma levels seem to reflect psoriasis activity, and treatment response, respectively. Fibroblasts are not a major source of increased IL-6 and IL-8 production in psoriasis.